1974
DOI: 10.1111/j.1476-5381.1974.tb09704.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Cholecystokinin Release by Bombesin in the Dog

Abstract: 1The intravenous infusion of bombesin elicited in the dog a contraction of the gall bladder with decreased opening pressure of the choledocho-duodenal junction and stimulation of pancreatic secretion. 2 The pancreatic juice -produced under the influence of bombesin was poor in bicarbonate and rich in protein. Threshold doses of the peptide were of the order of 0.25 ,ug kg-' h-1 and maximum protein output was obtained with 1 pg kg'1 h-1. The pancreatic protein response to bombesin was very similar, in its onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(34 citation statements)
references
References 9 publications
2
31
0
1
Order By: Relevance
“…However, it is also possible that at least the increase in gastric acid secretion is elicited by cholecystokinin released by bombesin. There is in fact strong evidence that bombesin besides releasing gastrin may also cause a release of cholecystokinin from the duodenal mucosa of the dog (Erspamer, Improta, Melchiorri & Sopranzi, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that at least the increase in gastric acid secretion is elicited by cholecystokinin released by bombesin. There is in fact strong evidence that bombesin besides releasing gastrin may also cause a release of cholecystokinin from the duodenal mucosa of the dog (Erspamer, Improta, Melchiorri & Sopranzi, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The Italian investigators have recently demonstrated that a perfusion of bombesin markedly stimulates the secretion of pancreatic juice rich in hydrolases in man (15), dog (16), and chicken (17). Erspamer et al (16) have suggested that the pancreatic response and the acceleration of gall bladder emptying (16,18) are secondary to the release of CCK-PZ from the duodenal mucosa.…”
Section: Ash-gln -Trp-ala-val-gly -His-leu -Met-nh2 + Litorin Pyr-glnmentioning
confidence: 99%
“…The tetradecapeptide bombesin, that can be isolated from amphibian skin, is a powerful stimulant of pancreatic secretion in several species including man (1)(2)(3)(4). Bombesin-like peptides are present in the mamReceivedfor publication 11 April 1977 and in revised form 6 July 1977. malian gastrointestinal tract (5,6).…”
Section: Introductionmentioning
confidence: 99%